2023
DOI: 10.1002/cne.25456
|View full text |Cite
|
Sign up to set email alerts
|

Functional topography of pulvinar–visual cortex networks in macaques revealed by INS–fMRI

Abstract: The pulvinar in the macaque monkey contains three divisions: the medial pulvinar (PM), the lateral pulvinar (PL), and the inferior pulvinar (PI). Anatomical studies have shown that connections of PM are preferentially distributed to higher association areas, those of PL are biased toward the ventral visual pathway, and those of PI are biased with the dorsal visual pathway. To study functional connections of the pulvinar at mesoscale, we used a novel method called INS–fMRI (infrared neural stimulation and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…To increase flexibility of stimulation patterns, we have developed a 100-fiber bundle array and have applied this to cortex in anesthetized monkeys, with plans to do so in awake monkeys 25,71 . Note that deep brain stimulators may also be designed 72,73 .…”
Section: Discussionmentioning
confidence: 99%
“…To increase flexibility of stimulation patterns, we have developed a 100-fiber bundle array and have applied this to cortex in anesthetized monkeys, with plans to do so in awake monkeys 25,71 . Note that deep brain stimulators may also be designed 72,73 .…”
Section: Discussionmentioning
confidence: 99%
“…INS stimulation of visual cortex in anesthetized macaque monkeys produced responses typical of visually induced cortical intrinsic signals 7 and furthermore led to selective modulation of functionally matched ocular dominance domains, consistent with activation of local cortico-cortical connections. The demonstration that INS stimulation in ultrahigh-field MRI could lead to activation of anatomically predicted mesoscale global brain sites in the macaque monkey further suggested that projection cells (excitatory pyramidal neurons) are being activated by INS [10][11][12] . These INS-induced responses have been shown to be intensityand duration-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the advantages of INS over conventional electrical stimulation include high spatial selectivity, contactless delivery, and importantly for primate and human application, neuromodulation of brain sites without prior opsin expression 8,9 . Furthermore, with this precision of targeted optical fiber stimulation and MRI compatibility, focal INS combined with MRI can be used for in vivo mapping of brain networks in primates [10][11][12] and holds promise for neuromodulation in awake behaving monkeys. While such applications have demonstrated great promise for circuit neuromodulation in vivo, its mechanism of action or effect on individual cell types is currently still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, brief (0.25msec) pulses of infrared (1875nm wavelength) light delivered (via 200um optical fiber) in pulse trains (200hz, duration 0.5sec) stimulate submillimeter clusters of neurons, leading to specific activation of connected sites whose locations are mapped at brainwide scale by recording Blood Oxygen Level Dependent (BOLD) signals (for review of INS, see (Chernov and Roe, 2014; Goyal et al, 2012; Thompson, 2014); for membrane capacitance effects see (Shapiro et al, 2012); for safety and damage thresholds in primates, see (Chernov et al, 2014; Pan et al, 2023)). As INS reveals functional connectivity, extending two synapses from the stimulation site (Xu et al, 2019), it evokes brainwide activations that prove to be highly anatomically and functionally specific (Shi et al, 2021; Yao et al, 2023). INS thus provides distinct benefits for high resolution brainwide circuit mapping compared with other electrical, optogenetic, and anatomical tracing methods (Klink et al, 2017; Roe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we established that the INS-fMRI method could be used to reveal statistically significant, mesoscale connectivity between subcortical nuclei and cortical areas (Shi et al, 2021; Yao et al, 2023). Our initial study of amygdala stimulation illustrated, via stimulation of a few sites in BA, the feasibility of detecting statistically significant BOLD signal at connected sites in the cingulate cortex and lateral sulcus areas (insular cortex and association sensory areas and auditory belt areas) (Shi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%